Does decision tree analysis predict oral ulcer activity-related factors in patients with Behçet's syndrome? - ÇANDERELİ, ZEHRA ÖZGE; ŞİŞMAN KİTAPÇI, NUR; AKSOY, AYSUN; ŞAHİN, ALİ; ALİBAZ ÖNER, FATMA; İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER; MUMCU, GONCA (My University, 2023)
OBJECTIVES: The study aimed to identify the interactions among treatment protocols and oral ulcer activity related factors in patients with Behçet\"s syndrome (BS) using the Classification and Regression Tree (CART) algorithm. METHODS: In this cross-sectional study, 979 patients with BS were included from16 centres in Turkey, Jordan, Brazil and the United Kingdom. In the CART algorithm, activities of oral ulcer (active vs. inactive), genital ulcer (active vs. inactive), cutaneous involvement (active vs. inactive), musculoskeletal involvement (active vs. inactive), gender (male vs. female), disease severity (mucocutaneous and musculoskeletal involvement vs. major organ involvement), smoking habits (current smoker vs. non-smoker), tooth brushing habits (irregular vs. regular), were input variables. The treatment protocols regarding immunosuppressive (IS) or non-IS medications were the target variable used to split from parent nodes to purer child nodes in the study. RESULTS: In mucocutaneous and musculoskeletal involvement (n=538), the ratio of IS use was higher in patients with irregular toothbrushing (ITB) habits (27.1%) than in patients with regular toothbrushing (RTB) habits (14.2%) in oral ulcer activity. In major organ involvement (n=441), male patients with ITB habits were more likely treated with IS medications compared to those with RTB habits (91.6% vs. 77.6%, respectively). CONCLUSIONS: Male BS patients on IS who have major organ involvement and oral ulcer activity with mucocutaneous and musculoskeletal involvement have irregular toothbrushing habits. Improved oral hygiene practices should be considered to be an integral part for implementing patient empowerment strategies for BS.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology